Queers non blanc·hes en France - Najwa Ouguerram-Magot (Glad!)
How can we explain the under-representation of queers of color in our queer activist spaces ? Are racialized people destined to be eternally taken for straight without a clear statement of their non-heterosexuality ? How excluding can be the coming out prerequisite in a non-heterosexual trajectory in terms of race ? Can we bring out specific experiences of non-heterosexual backgrounds for non-white people ? Based on a qualitative study conducted with six non-heterosexual persons with colonial diasporic backgrounds living in France, my research questions the experience of heterosexual/straight passing and what it reveals of the conflicting loyalties between race and sexuality that these queers of color face everyday. My first research results challenge the assumption of a universal (homo)sexual regime of visibility that only considers a eurocentric, out, open and explicit regime of visibility. Between submissive invisibility and resistant visibility, respondents defend another dissenting regime of visibility, reserved in its demonstration, implicit in its declaration. And even though it is not experienced as the proof of a frustrated relationship to their (homo)sexuality by the respondents, their regime (or choice) of visibility is constantly considered by their white queer environment to be the expression of a dysfunction.Eventually, for the respondents, it is not so much the homophobia present in their heterosexual/straight racialized spheres they need to defend themselves from, but rather the homonormativity of the largely white queer ones. Even though claiming to be queer can function as an act of resistance to the homonormativity of LGBT groups, liberal requirements persist within queer movements and feed neoliberal assimilationism, like the injunction to subscribe to a “queer way of being” through hypervisibility without questioning its underlying white standards. In postcolonial France, a country unwilling to deal with the contemporary consequences of its history, when two identities are set back-to-back, respondents openly choose to protect their racial community against homonationalist and homonormative discourses.